(untitled) (ENTHYMEMA, 2011)
The entry Verse and Prose, which Northrop Frye wrote for the Princeton Encyclopedia of Poetry and Poetics in 1974, builds on the remarks first developed by Frye in the “Manual of Style” chapter of The Well-Tempered Critic (1963), but it can also be read as an appendix to the fourth essay of Anatomy of Criticism (1957).